Pengaruh Media Sosial, Brand Image Dan Promosi Terhadap Penjualan Distro Pelangi Batu Aji Kota Batam - Sembiring, Nico Demus; ., Suhardi (Universitas Pamulang, 2024)
This research aims to investigate how social media, brand image and promotions influence sales of the Pelangi Batu Aji distro, Batam City. This population is taken based on the number of product sales in July 2023 which reached 186 consumers. In order to determine the sample, 127 respondents were selected using the Slovin formula method and sampling was carried out using simple random sampling. Data analysis in this research involves multiple linear regression, which includes data quality testing, classical assumption testing, influence testing, and hypothesis testing. The results of multiple linear regression analysis show that social media factors have an influence of 20.4% on sales. Brand image has an influence of 32.5% on sales. Promotions have an influence of 11.5% on sales. In order to explain the extent to which these factors influence sales, coefficient of determination (R2) analysis is used. The results show that social media, brand image and promotion factors together explain 68.8% of the variation in sales of the Pelangi Batu Aji distro, Batam City. Furthermore, the results of the t test and F test confirm that social media, brand image and promotion have a positive and significant influence on sales of the Pelangi Batu Aji distro, Batam City.